Comparison of Spatial Ability Between Male and Female Athletes - Putri, Azkane Adila; Lubis, Leonardo; Ong, Paulus Anam (Althea Medical Journal, 2017)
Background: Spatial ability is the ability to understand and memorize spatial relationship beneficial objects. This domain of cognition is crucial in sport activity for deciding strategy. Sex is one of the factors that determine spatial ability. This study aimed to determine the comparison of spatial ability between male and female athletes.Methods: This cross-sectional study was conducted by non-pairing comparative method. Data were taken on September 2015 in Indonesian National Sport Committee (Komite Olahraga Nasional Indonesia, KONI) Sport Center, Bandung, West Java, Indonesia. Spatial instrument used was Spatial Ability Test 1. Subjects were recruited from athletes of KONI, West Java, aged between 19-27 years old who were being trained for 19th National Sports Weeks (Pekan Olahraga Nasional, PON XIX) 2016. Mean value between male and female were compared using studies T-test with significance value (p)<0.05.Results: The total samples were 95 subjects, consisting of 44 males and 51 females. Results of the mean value in male were 29.16 (± 3.48) and female 28.80 (± 3.74).By using studies T-test, the significance outcome found was p = 0635 (p >0.05).Conclusions: There is no spatial ability differencesbetween male and female athletes of KONI, West Java DOI: 10.15850/amj.v4n2.1093